Design and verification of halogen-bonding system at the complex interface of human fertilization-related MUP PDZ5 domain with CAMK's C-terminal peptide. (February 2018) - Wang, Juan; Guo, Yunjie; Zhang, Xue
Graphical abstract: Highlights: A halogen-bonding system is designed at the complex interface of MUP PDZ5 with CAMK peptide. Halogen type and substitution position play critical role in the halogen-bonding strength. Bromine substitution at meta -position confers high affinity to the PDZ5–peptide binding. Abstract: Calmodulin-dependent protein kinase (CAMK) is physiologically activated in fertilized human oocytes and is involved in the Ca 2+ response pathways that link the fertilization calmodulin signal to meiosis resumption and cortical granule exocytosis. The kinase has an unstructured C-terminal tail that can be recognized and bound by the PDZ5 domain of its cognate partner, the multi-PDZ domain protein (MUP). In the current study, we reported a rational biomolecular design of halogen-bonding system at the complex interface of CAMK's C-terminal peptide with MUP PDZ5 domain by using high-level computational approaches. Four organic halogens were employed as atom probes to explore the structural geometry and energetic property of designed halogen bonds in the PDZ5–peptide complex. It was found that the heavier halogen elements such as bromine Br and iodine I can confer stronger halogen bond but would cause bad atomic contacts and overlaps at the complex interface, while fluorine F cannot form effective halogen bond in the complex. In addition, the halogen substitution at different positions of peptide's aromatic ring would result in distinct effects on the halogen-bonding system. The computational findings were then verified by using fluorescence analysis; it is indicated that the halogen type and substitution position play critical role in the interaction strength of halogen bonds, and thus the PDZ5–peptide binding affinity can be improved considerably by optimizing their combination.